Ecological consequences of the catastrophic destruction of the Kakhovka reservoir dam - Леонід Чорногор; Алла Некос; Ганна Тітенко; Леонід Чорногор (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія, 2024)
Formulation of the problem. The relevance is due to the need detail physical and mathematical modeling to the ecological consequences of the destruction of the Kakhovka Reservoir dam (Kherson region, Ukraine) on June 6, 2023.